The Impact of Intellectual Capital on Financial Performance Before, During, and After The Covid-19 Pandemic Crisis - Rahmawati, Tsania; Andayani, Endang Sri; Restuningdiah, Nurika (Journal of Applied Business, Taxation and Economics Research, 2024)
This study aims to investigate the impact of intellectual capital components, namely human capital, structural capital, relational capital, and capital employed on financial performance before, during, and after the COVID-19 pandemic crisis. This study analyzed 829 observation units from 168 non-financial Indonesian companies from 2018-2022. The data were analyzed using panel data regression with the help of EViews 13. The findings showed that in a 5-year period, only RC and CE significantly improve financial performance. However, only CE significantly improve financial performance before, during, and after the COVID-19 pandemic crisis. This indicates that non-financial Indonesian companies rely heavily on physical and financial capital investment in improving financial performance, both in non-crisis and crisis conditions. The findings offer implications for management and investors regarding the importance of optimizing IC investment, especially RC and CE efficiently to achieve high financial performance under uncertain conditions.